Nicotine pouches: a narrative review of the existing literature - Hajed M. Al-Otaibi; Hajed M. Al-Otaibi; Malik A. Althobiani; Malik A. Althobiani (Frontiers in Public Health)
IntroductionNicotine pouches are an emerging a non-combustible nicotine product. These tobacco-free oral products deliver nicotine through the gums. They are are viewed as potential alternatives to traditional tobacco and are marketed as safer alternatives.AimThis review evaluates the health-related effects, explore consumer behavior, understand usage trends, and consider regulatory perspectives of nicotine pouches, focusing on their potential role in harm reduction.ResultsNicotine pouches contain variable levels of nicotine (1–47 mg/pouch), with high pH values (median 8.8) that may increase nicotine bioavailability through the oral mucosa. Although they contain fewer harmful substances than traditional tobacco products, some types do contain harmful chemicals including formaldehyde, chromium, and tobacco-specific nitrosamines, which raise concerns about potential long-term health risks. Limited preliminary studies suggest reduced toxicant exposure compared to combustible tobacco, but the long-term health effects are still unknown. Consumer awareness significantly varies (7–47%) across populations, with higher usage noted among males, younger adults, and former tobacco users. On a global level, regulatory approaches differ, from total bans in some countries to minimum age requirements in others.ConclusionNicotine pouches are quickly becoming a popular alternative to traditional tobacco, providing potential harm reduction by containing fewer harmful constituents. However, they still contain the addictive substance nicotine and, in some cases, trace amounts of substances such as formaldehyde, which have been detected at very low levels, often near or below detection limits, and may not be considered a significant health risk according to some studies. Although they may aid existing smokers in harm reduction, there are still concerns about youth initiation, dual-use, marketing practices, and long-term oral and cardiovascular health effects. Inconsistent regulations, variable product quality, and a lack of longitudinal studies indicates a need for comprehensive research to guide evidence-based policies. Policymakers should prioritize standardized testing and marketing controls to safeguard public health, adopting a precautionary approach until long-term safety is established.